Mammals - Brownell, M. Barbara; Nang ChanYeema (Washington, D.C, USA The National Geographical Society, 1993)
Defines what mammals are and examines the characteristics and behavior of various primates, sea mammals, ungulates, rodents, marsupials, etc.
Keywords: Juvenile Nonfiction